Leadership strategies for the hybrid workforce best practices for fostering employee safety and significance - Ohlson, Matthew, 1974-; Goel, Lakshmi, 1979- (Advances in human resources management and organizational development (AHRMOD) book series., 2022)
"This book offers readers a collection of best practices on how to lead when people are working remotely or in a hybrid fashion, offering a blueprint on how to make people feel safe & significant in the workforce"--